The International Telematic University UNINETTUNO A Model of Cooperative & Work-Integrated Education through the New Technologies - Garito, Maria Amata (International Journal of Advanced Corporate Learning (iJAC), 2013)
Internet has completely changed the ways of producing and communicating knowledge. Today it is possible to attend University without any space or time limitation. The International Telematic University UNINETTUNO (UTIU) has been developing an organizational and psycho-pedagogical model and a technological structure, which, thanks to Internet, give everyone the possibility to attend the University anywhere in the world. Thanks to this model, UTIU has been committed in supporting the national socio-economic environment, through bilateral agreements and joint projects with trade unions and companies, in order to update and upgrade workersâ?? competences and to help them entering into the global markets. It is shown here the results of the outcomes deriving from an agreement signed with the Italian biggest telecommunication company: Telecom Italia. This agreement, which offers to Telecom Italiaâ??s employees the opportunity to enrol at UTIU degree programmes with the economic support of their employer, represents an innovative example of collaboration among a Company, a University and the Trade Unions, with the purpose of fostering human resourcesâ?? training and professionalization. The agreement derives from Telecom Italiaâ??s need for training its personnel. Thus, with the aim of improving their competences, Telecom Italia has counted on the innovative technologies provided by distance learning, acknowledging UTIUâ??s psycho-pedagogical model as the best solution available. As an innovative element, for the first time in the negotiation history the Trade Unions and a Company has agreed on the possibility for the employees to enrol for a degree programme, thus improving their social and cultural status.